Environment, society and international relations : towards more effective international environmental agreements - Kütting, Gabriela, 1967- (Routledge, 2000)
Written in an accessible and lively style, this ground-breaking text marries a critique of current remedies towards environmental problems to original and viable alternatives. This text adopts an eco-centric rather than a traditional environmental management perspective to focuses on the key issues such as: * The effectiveness of international agreements in solving environmental problems * the role of the structures and constraints within which these agreements operate.